Економічна оцінка витрат системи відновлення дорожньо-транспортної техніки - Голомовзий, Віктор; Калиновський, Андрій; Калиновська, Наталія (Видавництво Львівської політехніки, 2018)
The coefficient of efficiency is proposed for the economic assessment of the restoration of road - transport equipment, which allows establishing connection between costs and the received economic effect on recovery. This provides an opportunity to economically justify the optimal level of the restoration of road - transport equipment.
Economic cost estimate on the restoration of road-transportation equipment
Keywords: 658.58